"Alea iacta est" : (a case series report of problem and pathological gambling) - Koić, Elvira (Array, 2009)
Abstract: Gambling or gaming is a common term for a group of various games, activities and behavior that involve wagering money on an event with an uncertain outcome with the primary intent of winning additional money, i.e., a player risks and hopes to get back what he/she had gambled, or to win more. When the player is unable to resist impulses to gamble, and gambling behavior harmfully affects him or the others, then he/she is suffering from the so called »pathological gambling«, which is one of six categories of the »Impulse control disorders« in the International Classification of Diseases. Since, at present, there is no standardized program and approach to the problem of gambling in Croatia, and having in mind the arising accessibility and popularity of the »games of chance«, the authors are presenting seven cases of problem and pathological gambling and call for broad public discussion on the problem from medical-psychiatric and forensic-point of view. The first patient was treated on an outpatient basis with cognitive-behavioral and family therapy for problem gambling; for the second patient was treated for impulse control disorders; for the third patient gambling was a symptom of psychotic form of depressive disorder; the fourth had primary diagnosis of personality disorder; and the fifth patient was prosecuted for armed robbery and evaluated by a psychiatric expert. The sixth and the seventh patients were women suffering from primary bipolar affective and major depressive disorder, respectively. The authors conclude that, due to the size of the problem and its consequences, the prevention of pathological gambling is very important. The prevention can be carried out primarily through screening at the school level and primary health care services, whereas secondary screening may be conducted through the system of psychiatric care. It is recommended to invest into research, education of a wider population, and development of preventive programs